Nurses’ roles in preventing cardiotoxicity from Trastuzumab drug in HER-2 breast cancer patients - Pongthong,, Wanee; Aiamanan, Maneerat (Thai Journal of Nursing, 2020)
Currently, many different types of cancer had been treated with targeted therapy including HER-2 positive breast cancer. Targeted therapy is specific option for gene and protein expression of individual cancer cells. The most common drug used is Trastuzumab. The use of Trastuzumab drug, has the advantage in increasing survival rate for 10 years, but its adverse effect of cardiotoxicity, can be found among some patients. Therefore, the medical personnel must assess and monitor patients carefully during the treatment. Nurses could also prevent this adverse effect by providing proper discharge education on dietary, physical activity, follow-up coming for checking cardiac function and self-observation on warning signs and symptoms of cardiotoxicity in order to reduce severe complications e.g. congestive heart failure. As a result, these can increase quality of life in patients, reduce hospital length of stay as well as hospital cost.